Variation in relative palatability to sheep among Gliricidia sepium provenances - Larbi, Asamoah; Osakwe, I.I.; Lambourne, J.W. (Springer, 1993)
The cafteria technique using three-year-old West African Dwarf sheep was used to determine relative palatability differences within 28 provenances of Gliricidia sepium collected from west African and central America. Leucaena leucocephala and Guazuma ulmifolia were included as controls. Significant differences in relative palatability index were detected among G. sepium provenances. Mexican ecotypes appeared to be of low relative palatability compared to those from Costa Rica. Based on their RPI, provenances were grouped into high, medium and low preference rankings. The importance of the differences in relative palatability is dicussed in relation to Gliricidia-based alley farming in the humid West African region.